Fracture analysis on thin rotating disc with radial cracks - Wong, George Brendan Chong Yang (Nanyang Technological University, 2022)
Numerical methods were employed in stress and fracture analysis on thin rotating disc that operates at high speed. In recent years, thin rotating disc had been used widely in compressors and turbines of aircraft engines. The non-centralized holes on the disc give rise to stress concentration and crack was modelled in these high stress concentration locations under differentiating loading conditions. The normalized stress concentration factors and normalized stress intensity factors of the non-centralized holes are analyzed when subjected to loading such as radial tension and rotation. Variation in geometrical parameters will be used to investigate on how various parameters affect the Kt and KIc of the disc under loadings are obtained and presented. As for stress concentration analysis, maximum principal stress is located at the 180° region of the non-centralized holes for various parameters. Whereas, for stress intensity analysis, different crack length was modelled and are used to determine the stress intensity factor. In this investigation, generally noted that stress intensity factor and stress concentration factor decrease as the number of non-centralized holes increases.